Admission levels of asymmetric and symmetric dimethylarginine predict long-term outcome in patients with community-acquired pneumonia. Issue 1 (December 2017) - Vögeli, Alaadin; Ottiger, Manuel; Meier, Marc; Steuer, Christian; Bernasconi, Luca; Kulkarni, Prasad; Huber, Andreas; Christ-Crain, Mirjam; Henzen, Christoph; Hoess, Claus; Thomann, Robert; Zimmerli, Werner; et al.
Abstract Background During infection, there is an activation of the L-arginine-nitric-oxide pathway, with a shift from nitric oxide synthesis to a degradation of L-arginine to its metabolites, asymmetric and symmetric dimethylarginine (ADMA and SDMA). However, the prognostic implications for short-term or long-term survival remains unclear. We investigated the association of L-arginine, ADMA, and SDMA with adverse clinical outcomes in a well-defined cohort of patients with community-acquired pneumonia (CAP). Methods We measured L-arginine, ADMA, and SDMA in 268 CAP patients from a Swiss multicenter trial by mass spectrometry and used Cox regression models to investigate associations between blood marker levels and disease severity as well as mortality over a period of 6 years. Results Six-year mortality was 44.8%. Admission levels of ADMA and SDMA (μmol/L) were correlated with CAP severity as assessed by the pneumonia severity index (r  = 0.32, p  < 0.001 andr  = 0.56, p  < 0.001 for ADMA and SDMA, respectively) and higher in 6-year non-survivors versus survivors (median 0.62 vs. 0.48;p  < 0.001 and 1.01 vs. 0.85;p  < 0.001 for ADMA and SDMA, respectively). Both ADMA and SDMA were significantly associated with long-term mortality (hazard ratios [HR] 4.44 [95% confidence intervals (CI) 1.84 to 10.74] and 2.81 [95% CI 1.45 to 5.48], respectively). The effects were no longer significant after multivariate adjustment for age and comorbidities. No association of L-arginine with severity and outcome was found. Conclusions Both ADMA and SDMA show a severity-dependent increase in patients with CAP and are strongly associated with mortality. This association is mainly explained by age and comorbidities. Trial registration ISRCTN95122877 . Registered 31 July 2006.